2018
DOI: 10.1074/jbc.ra117.000667
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and proteoglycan link protein 1 (HAPLN1) activates bortezomib-resistant NF-κB activity and increases drug resistance in multiple myeloma

Abstract: Nuclear factor-κB (NF-κB) is a family of transcription factors that play a key role in cell survival and proliferation in many hematological malignancies, including multiple myeloma (MM). Bortezomib, a proteasome inhibitor used in the management of MM, can inhibit both canonical and noncanonical activation of NF-κB in MM cells. However, we previously reported that a significant fraction of freshly isolated MM cells harbor bortezomib-resistant NF-κB activity. Here, we report that hyaluronan and proteoglycan lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 58 publications
3
59
0
Order By: Relevance
“…HAPLN3 belongs to the hyaluronan and proteoglycan binding link protein gene family, which functions to maintain the extracellular matrix to support tissue architecture . Although this family of proteins has been previously found to be involved in drug resistance in multiple myeloma, the functional role of HAPLN3 in prostate epithelia is poorly understood, as are the consequences of DNA methylation at this locus . Their consistent hypermethylation levels in prostate cancer point to the importance of the further investigation to elucidate the roles for GAS6 and HAPLN3 in prostate biology and disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAPLN3 belongs to the hyaluronan and proteoglycan binding link protein gene family, which functions to maintain the extracellular matrix to support tissue architecture . Although this family of proteins has been previously found to be involved in drug resistance in multiple myeloma, the functional role of HAPLN3 in prostate epithelia is poorly understood, as are the consequences of DNA methylation at this locus . Their consistent hypermethylation levels in prostate cancer point to the importance of the further investigation to elucidate the roles for GAS6 and HAPLN3 in prostate biology and disease.…”
Section: Discussionmentioning
confidence: 99%
“…belongs to the hyaluronan and proteoglycan binding link protein gene family, which functions to maintain the extracellular matrix to support tissue architecture. 88 Although this family of proteins has been previously found to be involved in drug resistance in multiple myeloma, 89 (Table S4), whereas the threegene classifier would cut the misclassification rate by over two-fold, misclassifying only 124 men (67 FP and 57 FN) ( Table 3).…”
Section: Common Methylation Alterations In Prostate Cancermentioning
confidence: 99%
“…It is urgent to explore novel agents to overcome the drug resistance. NF-κB signaling pathway was found to play a signi cant role in the promotion of MM and bortezomib resistance (11,25). And inhibition of NF-κB pathway has been reported to be able to overcome bortezomib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite no evidence is available about a role of this transcription factor in the regulation of PVR gene expression in cancer cells, a search for sequence homology revealed the presence of putative NF-kB binding sites (-254- To identify possible molecular mediators involved in the upregulation of PVR by BMSCs, we focused our attention on NF-kB family transcription factors. These proteins are constitutively active in MM cells but a number of studies demonstrated increased NF-kB activity in MM cells in response to soluble factors produced by BMSCs [9,[39][40][41]. Despite no evidence is available about a role of this transcription factor in the regulation of PVR gene expression in cancer cells, a search for sequence homology revealed the presence of putative NF-kB binding sites (-254-GGGGAGGGCCAG-243; and -162-GTGGGTATTCCC-150) in the region of PVR(B) promoter spanning −343 bp from the transcription start site.…”
Section: Transcriptional Control Of Pvr Expression On MM Cells By Bmsmentioning
confidence: 99%